2011
DOI: 10.1103/physrevb.84.195453
|View full text |Cite
|
Sign up to set email alerts
|

Electron transport properties of bilayer graphene

Abstract: Electron transport in bilayer graphene is studied by using a first-principles analysis and the Monte Carlo simulation under conditions relevant to potential applications. While the intrinsic properties are found to be much less desirable in bilayer than in monolayer graphene, with significantly reduced mobilities and saturation velocities, the calculation also reveals a dominant influence of extrinsic factors such as the substrate and impurities. Accordingly, the difference between two graphene forms is more m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Unlike the gapped 2D semiconductors discussed in the present work, the change from linear to parabolic dispersion from monolayer to bilayer graphene (Supplementary Figure S17) results in the reduction of carrier mobilities. 29,30 Having identified the band-edge DOS as a key driver of the dimensionality crossover in the mobility of 2D materials, it will be interesting to investigate experimentally if the layer-dependent intrinsic carrier mobilities of 2D semiconductors could all fit into the simple description provided by our model.…”
mentioning
confidence: 99%
“…Unlike the gapped 2D semiconductors discussed in the present work, the change from linear to parabolic dispersion from monolayer to bilayer graphene (Supplementary Figure S17) results in the reduction of carrier mobilities. 29,30 Having identified the band-edge DOS as a key driver of the dimensionality crossover in the mobility of 2D materials, it will be interesting to investigate experimentally if the layer-dependent intrinsic carrier mobilities of 2D semiconductors could all fit into the simple description provided by our model.…”
mentioning
confidence: 99%
“…Energy band gap in BLG nanoribbon and nanoflake could be controlled by substrate properties and the applied vertical electric field, so these structures could be used as a channel material in carbon-based transistors [6][7][8][9][10][11][12] . Moreover, several studies have been performed, both theoretically and experimentally, on transport properties in BLG structure [6][7][8][9][12][13][14][15][16][17] . Interestingly, BLG field-effect-transistors with high on/off current ratios at room temperature have been reported 9 .…”
Section: Introductionmentioning
confidence: 99%
“…F. Xia et al reported on/off ratios of ∼100 and 2000 at room temperature and 20 K using dual‐gate bilayer graphene transistors, corresponding to an bandgap of >0.13 eV at an average electric displacement of 2.2 Vnm −1 179. Revealing the large bandgap in bilayer graphene may enable the nanoelectronic and nanophotonic applications, meanwhile, a recent theoretical study shows that bilayer graphene has a lower carrier mobility and saturation velocity than monolayer graphene, due to stronger acoustic‐phonon scattering, weaker optical‐phonon scattering, and nonlinear dispersion at the bottom of the conduction band 180. The charged impurity scattering in bilayer graphene has a greater effect on decreasing the drift velocities than that in monolayer one.…”
Section: Performance Controlmentioning
confidence: 99%